2018
DOI: 10.1016/j.jss.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

MC1R gene polymorphisms are associated with dysfunctional immune responses and wound infection after burn injury

Abstract: Background: Systemic inflammatory response syndrome (SIRS) is associated with organ failure and infectious complications after major burn injury. Recent evidence has linked melanocortin signaling to anti-inflammatory and wound-repair functions, with mutations in the melanocortin 1 receptor (MC1R) gene leading to increased inflammatory responses. Our group has previously demonstrated that MC1R gene polymorphisms are associated with postburn hypertrophic scarring. Thus, we hypothesized that MC1R single nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Chronic infectious wounds refer to wounds (due to various factors) infected with microorganisms during the healing stage, which are common in surgery 5 - 7 . The recovery of chronic infectious wounds is intractable, which is prone to delayed wound healing or even unhealed wounds, seriously affecting the daily life of patients 8 - 10 . In addition, long-term unhealed wounds will cause severe pain, affecting the psychological state and sleep status of patients 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infectious wounds refer to wounds (due to various factors) infected with microorganisms during the healing stage, which are common in surgery 5 - 7 . The recovery of chronic infectious wounds is intractable, which is prone to delayed wound healing or even unhealed wounds, seriously affecting the daily life of patients 8 - 10 . In addition, long-term unhealed wounds will cause severe pain, affecting the psychological state and sleep status of patients 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its widely accepted roles in pigmentation, the MC1R gene has also been correlated with anxiety, being seen as a significant predictor of dental care-related anxiety in humans (Binkley et al, 2009). The MC1R gene has also been implicated in burn injury complications, with human studies showing MC1R polymorphisms may contribute to systemic infectious response syndrome associated with infectious complications and organ failure following major burn injury (Carter et al, 2018). Pheomelanin pigment pathways resultant from MC1R polymorphisms have also been attributed to ultraviolet-radiation independent melanoma carcinogenesis via a mechanism of oxidative damage, with variants presenting the highest melanoma risk (Chen et al, 2017a(Chen et al, , 2017bMitra et al, 2012;Tell-Marti et al, 2020).…”
Section: Pleiotropic Effects Of the Melanocortin-1 Receptormentioning
confidence: 99%
“… 11 Carter found that the melanocortin 1 receptor ( MC1R ) gene polymorphism was associated with wound infection after burn injury. 12 In the repair stage after burn injury, nucleotide-binding domain leucine-rich repeat ( NLR ) and pyrin domain containing receptor 3 ( NLRP3 ) promote wound healing through regulation of macrophage polarization and inflammation. 13 However, there has been little information regarding the important genes expressed during burn shock.…”
Section: Introductionmentioning
confidence: 99%